AFIKS (Suatu Kajian Morfologi Bahasa Gorontalo) - Luwuti, Sri Rumiyatiningsih (Jurnal Pelangi Ilmu, 2009)
This aim of this writing is present the enlightenment of morpholohgy relatet with Gorontalesse language affixes. In this writing also ts current the significance difference about the concept of affix in Gorontalo and Indonesia language. That importance divergence is found in time concept.